2019
DOI: 10.1007/s00484-019-01781-3
|View full text |Cite
|
Sign up to set email alerts
|

Alder pollen concentrations in the air during snowfall

Abstract: The focus of our study was airborne alder pollen because it is one of the main causes of inhalant allergies in many countries in the Northern Hemisphere. The main research setback was pollen concentrations during snowfall. Analyses from a 21-year database showed that the hourly patterns of occurrence of airborne Alnus pollen during snowfall differ. Snowfall can cause a decrease in pollen concentrations in the air that may persist for several hours. However, during the snowfall period of 2018, an increase in po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
3
4
0
Order By: Relevance
“…From further examination of the monthly correlation, a notable decline in temperature was noted following June/July when most pollen types were in decline. This supports previous findings that temperature dependence decreases following peak pollen season (Khwarahm et al, 2014 ). In 2018 a notable increase in temperature dependence was seen in September during which most pollen types were in steady decline, representing a period of resuspension (Rojo et al, 2020 ).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…From further examination of the monthly correlation, a notable decline in temperature was noted following June/July when most pollen types were in decline. This supports previous findings that temperature dependence decreases following peak pollen season (Khwarahm et al, 2014 ). In 2018 a notable increase in temperature dependence was seen in September during which most pollen types were in steady decline, representing a period of resuspension (Rojo et al, 2020 ).…”
Section: Discussionsupporting
confidence: 93%
“…As a result, the expected release of arboreal pollen in late March was significantly reduced as was the summer release of Poaceae pollen. This corroborates results from similar studies where colder temperatures during early spring were linked to a delay and reduction in arboreal pollen release (Emberlin et al, 2002;Kasprzyk & Borycka, 2019) and a reduction in summertime Poaceae concentrations (Makra et al, 2012). A study by Emberlin et al (1999) observed a comparable correlation between the soil temperature in early spring and the abundance of grass pollens released during the following summer, corroborating the increased Poaceae pollen concentrations seen for the 2019 season.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations